ENVIRONMENTAL FACTORS AND HEALTH OF THE POPULATION OF THE ARAL SEA REGION OR IN THE CONDITIONS OF KARAKALPAKSTAN (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article explores the complex relationship between environmental factors and population health in the Aral Sea region, with a focus on the specific conditions of Karakalpakstan. The study uses a multidisciplinary approach combining literature analysis, environmental monitoring, and health data to comprehensively understand the impact of the environmental crisis on societal well-being. The findings are intended to provide valuable information to policymaker’s authorities and stakeholders to develop effective strategies to reduce health risks in regions affected by environmental degradation.